Threatened Reef Corals of the World - Huang, Danwei (PloS one, 2012)
A substantial proportion of the world's living species, including one-third of the reef-building corals, are threatened with extinction and in pressing need of conservation action. In order to reduce biodiversity loss, it is important to consider species' contribution to evolutionary diversity along with their risk of extinction for the purpose of setting conservation priorities. Here I reconstruct the most comprehensive tree of life for the order Scleractinia (1,293 species) that includes all 837 living reef species, and employ a composite measure of phylogenetic distinctiveness and extinction risk to identify the most endangered lineages that would not be given top priority on the basis of risk alone. The preservation of these lineages, not just the threatened species, is vital for safeguarding evolutionary diversity. Tests for phylogeny-associated patterns show that corals facing elevated extinction risk are not clustered on the tree, but species that are susceptible, resistant or resilient to impacts such as bleaching and disease tend to be close relatives. Intensification of these threats or extirpation of the endangered lineages could therefore result in disproportionate pruning of the coral tree of life.